Consultancy services in the Middle East construction - Alerasoul, Sepehr (2013)
Presently, clients seek the services of the consultants to implement the projects. Some of the clients do not have enough technical staff to implement the project therefore they need the services of the consultants. In the Middle East, the consultants worked together as a consortium. However, some of the clients are not satisfied with the services as provided by this consortium of consultants. The aim of this study is to examine the services provided by the consultants in the construction industry. The objectives of the study are to study the services as provided by various consultants, to identify the methods of selection of the consultants by the clients, to identify the problems faced by consultants in project implementation and to determine the level of satisfaction of client regarding the services provided by the consultants. The study is carried out on consultants (consortium) involved in civil and building projects in Iran. The data is collected through questionnaires and interviews. The data is analyzed using statistical analysis and average index. From the study, the services provided by the consultants are in the framework that included architecture, services engineering (Electrical & Mechanical), project management, structural & civil engineering. The ways of selection of the consultants by the clients are based on experience, quality and cost (QCBS) and political influence. The problems faced by the consultants are late payment of fees by the client, currency fluctuation and lack of support from client. The level of satisfaction of the clients regarding the services as provided by the client is “satisfied”.